Opportunities for Learning-based Conversations in High School Mathematics - McFeetors, Janelle (Alberta Journal of Educational Research, 2016)
Conversations as moments for interpersonal and intimate turning round of ideas for the purpose of growth are well-defined within curriculum inquiry. Interactions among grade 12 students in this study demonstrate the possibility of learning to learn mathematics through conversation. Attending to opportunities for learning-based conversations, constructivist grounded theory supported developing a Model of Providing Opportunities for Learning-based Conversations. Four features of preparation, presence, mode, and pacing represent a space where students could improve their learning through connectedness among conversational moments. Understanding how conversational opportunities were offered could empower others to engage in learning-based conversations with their students. La recherche pédagogique explique clairement comment les conversations peuvent représenter des discussions interpersonnelles et intimes, des moments qui favorisent l’épanouissement. Cette étude a trouvé que les interactions parmi des élèves de la 12e année peuvent illustrer dans quelle mesure les conversations aident à apprendre comment apprendre les mathématiques. Attentifs aux occasions d’entretenir des conversations reposant sur l’apprentissage, nous nous sommes appuyés sur la théorie constructiviste pour développer un modèle visant la création d’occasions pour les conversations reposant sur l’apprentissage. Les quatre composantes – la préparation, la présence, le mode et le rythme – représentent un espace où les élèves peuvent améliorer leur apprentissage en tissant des liens entre leurs conversations. En comprenant comment offrir des occasions pour le développement de conversations reposant sur l’apprentissage, nous pouvons habiliter les autres à participer aux conversations reposant sur l’apprentissage avec leurs élèves.